Neuroaesthetics A Methods-Based Introduction - Balinisteanu, Tudor; Priest, Kerry (Springer International Publishing : Imprint: Palgrave Macmillan, 2024)
This open access neuroaesthetics textbook, the first in the world, is designed for teaching a semester module (14 meetings) to undergraduate/masters students from both the sciences and the humanities. Written in a style that appeals to humanities students without prior science training, and to science students without prior humanities training, the textbook contains 6 Units, material for an introductory class, and summative comments to be discussed in a closing meeting. Each Unit comprises an overview designed as student home reading, a lecture, and a lab. The labs contain detailed step-by-step instructions for running a basic experiment and analysing the collected data, that can be easily implemented in humanities and science departments alike. The textbook introduces students to philosophical considerations of neuroaesthetics topics in context of the history of empirical aesthetics, showcases experimental approaches to the empirical study of dance, the visual arts, and music, and supports hands-on training in experimental research methods. Tudor Balinisteanu is a Research Fellow at University of Suceava, Romania, and established the first Neuroaesthetics Lab in Romania. He is currently researching empathy through leading participation in international projects including PoeticA, focusing on the biological universals of the aesthetic experience of poetry, Origins of Dance, focusing on the origins of rhythm in mutual entrainment, and VIVAET, that aims to create empathic visual identities for medical AIs. Kerry Priest is an interdisciplinary artist and visiting specialist in music at the University of Plymouth, UK. She has previously taught at Von Humboldt University, Germany and the University of Eichstaett-Ingolstadt. Her poetry has been published widely and she has written libretti for the Royal Opera House and stage work for the Minack Theatre.